2014
DOI: 10.1097/jto.0000000000000069
|View full text |Cite
|
Sign up to set email alerts
|

EGFR Mutation and Brain Metastasis in Pulmonary Adenocarcinomas

Abstract: We found a significant association between EGFR mutation and risk of brain metastases at the time of diagnosis and follow-up after curative resection for pulmonary adenocarcinoma. This result indicates the distinct clinical features of EGFR-mutated tumors in terms of brain metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
180
3
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 266 publications
(207 citation statements)
references
References 30 publications
10
180
3
2
Order By: Relevance
“…As known, EGFR mutations, being deemed to be a biological marker of NSCLC in recent decades, account for 10%‐25% of NSCLC 53. As a result of its constitutive activation of EGFR signaling and oncogenic transformation, EGFR was confirmed to be an independent risk factor and served as a crucial role 54. So, it is meaningful to evaluate metastatic characteristics in patients with EGFR mutation during clinical screening and treatment 55…”
Section: The Mechanism Of Brain Metastasismentioning
confidence: 99%
“…As known, EGFR mutations, being deemed to be a biological marker of NSCLC in recent decades, account for 10%‐25% of NSCLC 53. As a result of its constitutive activation of EGFR signaling and oncogenic transformation, EGFR was confirmed to be an independent risk factor and served as a crucial role 54. So, it is meaningful to evaluate metastatic characteristics in patients with EGFR mutation during clinical screening and treatment 55…”
Section: The Mechanism Of Brain Metastasismentioning
confidence: 99%
“…Dong-Yeop Shin et al previously reported that the frequency of EGFR mutation was statistically higher for patients with brain metastases than those without brain metastases, and a strong association between EGFR mutation status and brain metastasis was observed (adjusted odds ratio = 3.83, p = 0.001) 22) . A unique intracranial metastasis system might be suggested in EGFR-mutated NSCLC patients.…”
Section: Discussionmentioning
confidence: 99%
“…RTOG 0933 was a single-arm phase II study of radiotherapy for brain metastasis, and the results from this study showed that hippocampal-avoidance WBRT was associated with preservation of memory and QOL as compared with historical series (46). Notable, patient with EGFR mutation has the relatively high risk of developing brain metastases, and the reported intracranial progression during the course of TKI therapy is approximately 30% (39). Therefore, it is interesting to explore the role of PCI in the patients treated with TKIs, provided that preservation of memory and QOL can be ensured with modern radiotherapy techniques.…”
Section: Prophylactic Cranial Irradiation (Pci)mentioning
confidence: 99%
“…Of note, the risk of brain metastases is relatively high in patients with EGFR mutation at the time of diagnosis, as well as during the course of follow up in those who administrated with surgery. Shin et al reported a dramatic correlation of EGFR mutation status and brain metastasis (adjusted odds ratio =3.83, P=0.001) in 314 patients with testing of EGFR mutation and brain magnetic resonance imaging at diagnosis (39). In this study, they also found that, in a subgroup analysis of 133 patients treated with surgical resection, EGFR mutation status was a poor prognostic factor for the risk of brain metastasis [hazard ratio (HR) =4.49, P=0.026] after adjustment for pathologic N stage.…”
Section: Brain Metastasis and Egfr Mutationmentioning
confidence: 99%